Fuzzy Control on Artificial Ripening of Uli Banana - . Sugiyono; . Sutrisno; Budi I. Setiawan (Jurnal Keteknikan Pertanian, 1999)
Banana is a potential commodity to gain foreign currency since its export has tended to increase yaer by year. Postharvest handling of banana is very important in order to maintain high quality of the products. Artificial ripening is one method applied to control the rate of ripening and in the other side to guarantee the uniformity of quality. Teperature in the ripening chamber plays an important role since it directly influences respiration rate of the products. This research is aimed to apply fuzzy control to regulate the temperature, which is set in order to get better quality of the product. Yhe objective of the fizzy control is to set the temperature into 4 (four) decreasing steps : 1) 24"C. 2)22.5"C 30 21.5 "C and 4) 24 "C each for 24 hours. Respiration rate during these periods are 0.0866 ml CO2/kg/h become 0.06054 ml CO2/kg/h or 3.1716 ml O2/kg/h/ become 0.7016 ml O2/kg/h.